Pathomechanisms of Paraneoplastic Myasthenia Gravis - Philipp Ströbel; Tobias Preisshofen; Markus Helmreich; Hans Konrad Müller-Hermelink; Alexander Marx (Clinical and Developmental Immunology)
Thymic T cell development is characterized by sequential selection processes to ensure generation of a self-tolerant, immuncompetent mature T cell repertoire. Malfunction of any of these selection processes may potentially result in either immunodeficiency or autoimmunity. Myasthenia gravis (MG) is a typical autoimmune manifestation of thymic epithelial tumors (thymomas) and is related to the capacity of these tumors to generate and export mature T cells. Analysis of the factors that lead to autoimmunization in thymomas will help to understand the mechanisms that prevent MG under physiological conditions in humans. In a comparison of MG(+) and MG(-) thymomas, we could show that only thymomas capable of generating mature CD45RA+CD4+ T cells are associated with MG (p< 0.0001), while terminal thymopoiesis was abrogated in MG(-) thymomas. In particular, acquisition of the CD27+CD45RA+ phenotype appears to be a critical checkpoint of late T cell development in the human thymus and may play an important role in the prevention of autoimmunity. Moreover, MG(-) thymomas were virtually depleted of regulatory (CD4+CD25+) T cells (regT), while regT were readily detectable in MG(+) thymomas, albeit at significantly reduced numbers compared to control thymuses. Thus, in MG(+) thymoma patients, thymectomy apparently also results in removal of a regulatory T cell pool and may explain the frequent temporary postoperative deterioration of MG in these patients.